2007
DOI: 10.1007/s00296-007-0493-4
|View full text |Cite
|
Sign up to set email alerts
|

Isokinetic evaluation of knee extensor/flexor muscle strength in patients with hypermobility syndrome

Abstract: Benign joint hypermobility syndrome (BJHS) is a syndrome with musculoskeletal pain originating from the increased laxity of the joints and the ligaments. The study was to compare the isokinetic strength of knee extensor/flexor muscles of BJHS patients with healthy controls. Forty patients diagnosed as having BJHS with Brighton criteria and 45 years of age, height and weight-matched healthy controls were recruited for the study. Isokinetic testing was performed with isokinetic dynamometry of Biodex System 3Pro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
1
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 37 publications
1
51
1
3
Order By: Relevance
“…dancers) and symptomatic forms of GJH (e.g. EDS-HT, hypermobility syndrome) [19][20][21] In these studies, muscle weakness was found to be associated with pain [22] and fatigue. [21] However, whether these factors moderate the association between muscle strength and activity limitations is unknown.…”
Section: Introductionmentioning
confidence: 89%
“…dancers) and symptomatic forms of GJH (e.g. EDS-HT, hypermobility syndrome) [19][20][21] In these studies, muscle weakness was found to be associated with pain [22] and fatigue. [21] However, whether these factors moderate the association between muscle strength and activity limitations is unknown.…”
Section: Introductionmentioning
confidence: 89%
“…[24][25][26][27] A recent systematic review and meta-analysis has also confirmed the impact of JHS on a range of psychological variables such as fear, agoraphobia, anxiety, depression and panic disorders. 28 Physiotherapy, particularly exercise, is generally considered the mainstay of treatment, 2,8,9,15,[29][30][31] and professionals in a number of centres in the UK have developed a specialist interest in treating people with JHS.…”
Section: Fundingmentioning
confidence: 99%
“…Empirical data has shown that, when compared with healthy controls, JHS has a significant impact on outcomes such as exercise endurance, gait, pain, proprioception, strength, function and quality of life both in children [7,8,9,10] and adults [11,12,13,14]. A recent systematic review and meta-analysis confirmed the 5 impact of JHS on a range of psychological variables such as fear, agoraphobia, anxiety, depression and panic disorders [15].…”
Section: Introductionmentioning
confidence: 87%